Efektivitas Pelayanan Publik Dalam Pembuatan Kartu Identitas Penduduk Bilhete De Identidade ( BI) Di Kantor Justica Dili Timor- Leste - Doutel, Pascoal Barros; Yasintha, Putu Nomy; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER; Vol 1 No 01 (2021): Administrasi Publik 2021, 2021)
The Government of Timor-Leste, through the Ministry of Justice (Ministério da Justiça), as one of the main functions of the government, is to provide the publishing service of the Bilhette de Identidade. However, in its implementation there are still some problems, such as technical problems related to the use of infrastructure that hampers services to procedural problems. The purpose of this study was to determine the effectiveness of services by using the theory of effectiveness according to Duncan. The study used a qualitative descriptive method. The results of the study show that effectiveness has not been maximally achieved, especially on the integration indicators. Meanwhile, the indicators for achieving goals and adaptation have met the criteria for determining service effectiveness. Keywords: Effectiveness, Service, Bilhette de Identidade